2015
DOI: 10.1111/zph.12204
|View full text |Cite
|
Sign up to set email alerts
|

Food Safety Hazards and Microbiological Zoonoses in European Meat Imports Detected in Border Inspection in the Period 2008–2013

Abstract: Microbiological contaminations and other food safety hazards are omnipresent within the European Union (EU) and a considerable risk for consumers, particularly in imported meat and meat products. The number of rejections at external EU borders has been increasing in recent years. Official authorities in each member state are therefore obliged to notify border rejections of food and animal feed due to a direct or indirect risk to human or animal health. This study explored the trends and temporal and spatial di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…During 2013, approximately 90 border rejection cases were reported for chilled beef coming from different countries [ 13 ]. Since fecal contamination of meat during processing at abattoirs is unavoidable [ 66 ], zero tolerance intervention measures should be applied to all STEC in meat, together with GMP and HACCP [ 39 ]. Arthur et al [ 33 ], in a study of large processing plants in the US, demonstrated that STEC prevalence dramatically diminished (58.3%–8.3%) in carcasses previously treated with different antimicrobial intervention strategies such as steam vacuuming, hot water washing, organic acid washing and steam pasteurization.…”
Section: Discussionmentioning
confidence: 99%
“…During 2013, approximately 90 border rejection cases were reported for chilled beef coming from different countries [ 13 ]. Since fecal contamination of meat during processing at abattoirs is unavoidable [ 66 ], zero tolerance intervention measures should be applied to all STEC in meat, together with GMP and HACCP [ 39 ]. Arthur et al [ 33 ], in a study of large processing plants in the US, demonstrated that STEC prevalence dramatically diminished (58.3%–8.3%) in carcasses previously treated with different antimicrobial intervention strategies such as steam vacuuming, hot water washing, organic acid washing and steam pasteurization.…”
Section: Discussionmentioning
confidence: 99%
“…The European Union (EU) strives for a high level of food safety in order to ensure consumer health and, thus, a range of directives and regulations regarding the import of food were established. Microbiological criteria concerning meat products as well as all related imports to the EU were defined in Regulation (EC) 2073/2005 while Regulation (EC) No 206/2009 lays down strict rules and measures for the illegal import of products of animal origin in personal consignments [5]. Nevertheless, substantial amounts of meat products are introduced illegally into the EU each year, circumventing any controls.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, also the awareness of food safety hazards needs to be heightened, as even contaminations with “harmless” bacteria like E . coli can be of concern [ 5 , 7 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…coli and Salmonella spp. have been isolated frequently from transcontinentally traded meat [ 5 ]. However, illegally imported products of animal origin (POAO) may also harbour zoonotic pathogens which pose an additional risk for public health, especially in case of uncommon strains [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%